Atomized inhalation of indocyanine green in thoracoscopic surgery for intralobar pulmonary sequestration: a multicenter study - Ye Yin; Guofeng Zhang; Wei LI; Didi Zhuansun; Xiaofeng Xiong; Yanan Li; Yin He; Wenjing Wang; Tianqi Zhu; Jiexiong Feng (Respiratory Research)
Abstract Background Investigate the safety and efficacy of preoperative atomization inhalation of indocyanine green (ICG) solution in precise lesion resection of pediatric thoracoscopic intralobar pulmonary sequestration. Methods A multicenter 1:1 matched case-control study was adopted, to compare the safety and efficacy of the ICG group (preoperative atomization inhalation of 0.5 mg/kg ICG solution) with traditional group (no preoperative atomization inhalation of ICG solution). The baseline, intraoperative, and postoperative recovery conditions of the two groups were observed. Outpatient follow-up visits were conducted 3 to 6 months after surgery, including lung CT scans and pulmonary ventilation function tests. Results 134 patients were included in the study. The ICG group included 67 patients, and the traditional surgery group included 67 patients matched at a ratio of 1:1 according to age and lesion location. There were no reports of deaths or adverse reactions. The postoperative chest drainage tube indwelling time [(53.19 ± 8.15) hours vs. (73.25 ± 15.51) hours, P < 0.001] and postoperative hospital stay [(4.81 ± 1.84) days vs. (6.72 ± 1.31) days, P < 0.001] were shorter in the ICG group than in the traditional group. More importantly, the postoperative pulmonary function in the ICG group was better than that in the traditional group. No residual lesions were found in the postoperative CT examination of both groups. Conclusions The innovative application of atomization inhalation of ICG provides the possibility for precise localization and lesion resection of pediatric thoracoscopic intralobar pulmonary sequestration. This maximizes the preservation of normal lung parenchyma, better improves postoperative pulmonary function, and shortens postoperative recovery time.